Effects of Different Levels of Pigeon Egg Yolk in Extenders on the Post-Thaw Semen Quality of Sahiwal Bulls - Hafez Jamil-ur-Rahman, Nazir Ahmad*, Najib-ur-Rahman, Salman Waheed, Maqbool Ahmad, Muhammad Younis1 and Tanveer Ahmad2 (Pakistan Veterinary Journal, 2012)
In this study, effects of replacing chicken egg yolk (CEY) with pigeon egg yolk (PEY) in extenders on post-thaw semen quality in Sahiwal bulls were investigated. Attempts were also made to see if post thaw semen quality was affected by reducing PEY level in the extender. Twenty four semen samples were diluted with five Tris-based extenders. Extender A contained 20% CEY and was used as control, while extenders B, C, D and E contained 5, 10, 15 and 20% PEY, respectively. After freezing and storage for 24 hrs in liquid nitrogen, these samples were evaluated for post-thaw semen quality parameters.The difference in post extension sperm motility between extenders A (20% CEY) and E (20% PEY) was non significant. Post extension sperm motility decreased as the level of PEY in the extender was decreased. A similar trend was recorded for post thaw sperm motility, livability, absolute index of livability and sperm with intact plasma membrane. The percentages of spermatozoa with abnormal head, or tail were lower (P<0.01) in control extender A and extender E compared to extenders B, C and D. However, for abnormal mid-piece, extenders A and E showed lower values than extender C only. It was concluded that replacing CEY with PEY in same concentration (20%) did not improve post thaw semen quality. Moreover, reducing the concentration of PEY in semen extender from 20 to 5% had adverse effects on post-thaw quality of Sahiwal bull semen.